The Business Analysis of Acacia auriculiformis Agroforestry in Batulanteh Forest Management Unit, Sumbawa, West Nusa Tenggara - Yonky , Yonky Indrajaya; Siarudin, Mohamad Siarudin (Forestry Department, University of Muhammadiyah Makassar, 2021)
The utilization of land together between trees and crops is one of the strategies in land rehabilitation program in Indonesia. High pressure from people living surrounding the forest land required the forest managers to invite more participation from the people in managing the forest land. Agroforestry pattern with certain tree species chosen by forest managers together with certain crops preferred by the communities may become the solution for all stakeholders’ interests in a high-pressured forest area. One of the considerations in agroforestry development is economic aspect. This study aims to analyze the financial feasibility of agroforestry pattern auri (Acacia auriculiformis) and peanut, pigeon pea, and corn in Batulanteh forest management unit (FMU) in Sumbawa, West Nusa Tenggara. The feasibility assessment criteria used in this study were Net Present Value (NPV), Internal Rate of Return (IRR) and Benefit Cost Ratio (BCR). The result of this study showed that agroforestry pattern of auri with paddy, peanut, pigeon pea and corn is financially feasible with the NPV, IRR and BCR values are IDR14.607.837.-, 53 % and 1.51 respectively.